2016
DOI: 10.1504/ijmc.2016.075019
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mobile consumers' perceived value of location-based advertising and user responses

Abstract: This study examines factors affecting mobile consumers' perceived advertising value of latest location-based mobile advertising (LBA) and its relationship with user responses. The national web survey recruits 605 respondents who fit demographic quotas of mobile consumers in Singapore. PLS (Partial Least Squares) results show that privacy concerns have a stronger negative effect on perceived LBA value than perceived sacrifice, while perceived utility, utilizing contextual information, and trust positively predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 37 publications
2
66
0
Order By: Relevance
“…M-commerce is born out of the explosive development of cell phone, and it has the potential of allowing customers to access the internet anywhere, anytime for M-commerce business. Hence, the issues related to consumer's decision-making on M-commerce have important implications for M-commerce service providers and for academic researchers (Choi et al, 2008;Chong, 2013a;Lin, Paragas and Bautista, 2016;Hwang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…M-commerce is born out of the explosive development of cell phone, and it has the potential of allowing customers to access the internet anywhere, anytime for M-commerce business. Hence, the issues related to consumer's decision-making on M-commerce have important implications for M-commerce service providers and for academic researchers (Choi et al, 2008;Chong, 2013a;Lin, Paragas and Bautista, 2016;Hwang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, most recent industrial studies have reflected that there is a big opportunity for mobile operators to leverage on mobile advertising, as a revenue stream in the next coming years [42], [43]. However, the mobile operators are struggling, as some stakeholders are not satisfied with the advertising services in their current form, where some of their needs are overlooked [44].…”
Section: ) Mobile Advertising Platformmentioning
confidence: 99%
“…A sample of these findings is presented in Table IV to show how the themes emerged based on valid results. [10], [44], [48] In summary, the mobile advertising still has significant potential, but in case of MNOs, the SMS and location-based advertising (LBA) current models suffer from some obstacles that hinder them from reaching their maximum potential as industrial reports indicated. The advertisers' need data about their advertising activities to help them evaluate and assess their investments as compared to the dominated parties such as Google, Facebook, and others [45].…”
Section: ) Mobile Advertising Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…Survey questions were adopted and adapted from existing studies on mobile, online news, and location-based services use (Lin et al 2016;Liu et al 2012;Merisavo et al 2007;Pew Research Center, 2015b;Pew Research Center, 2017;Wei et al 2010). In addition, questions from the U.S. Census (American Community Survey, 2017) were used for the demographic section of the questionnaire.…”
Section: Questionnairementioning
confidence: 99%